A Comprehensive Map of Intron Branchpoints and Lariat RNAs in Plants. Issue 5 (20th March 2019) - Zhang, Xiaotuo; Zhang, Yong; Wang, Taiyun; Li, Ziwei; Cheng, Jinping; Ge, Haoran; Tang, Qi; Chen, Kun; Liu, Li; Lu, Chenyu; Guo, Junqiang; Zheng, Binglian; et al.
Abstract : Analysis of 948 RNA sequencing data sets produced a comprehensive map of intron branchpoints and lariat RNAs in Arabidopsis thaliana, tomato, rice, and maize. Abstract: Lariats are formed by excised introns, when the 5′ splice site joins with the branchpoint (BP) during splicing. Although lariat RNAs are usually degraded by RNA debranching enzyme 1, recent findings in animals detected many lariat RNAs under physiological conditions. By contrast, the features of BPs and to what extent lariat RNAs accumulate naturally are largely unexplored in plants. Here, we analyzed 948 RNA sequencing data sets to document plant BPs and lariat RNAs on a genome-wide scale. In total, we identified 13, 872, 5199, 29, 582, and 13, 478 BPs in Arabidopsis ( Arabidopsis thaliana ), tomato ( Solanum lycopersicum ), rice ( Oryza sativa ), and maize ( Zea mays ), respectively. Features of plant BPs are highly similar to those in yeast and human, in that BPs are adenine-preferred and flanked by uracil-enriched sequences. Intriguingly, ∼20% of introns harbor multiple BPs, and BP usage is tissue-specific. Furthermore, 10, 580 lariat RNAs accumulate in wild-type Arabidopsis plants, and most of these lariat RNAs originate from longer or retroelement-depleted introns. Moreover, the expression of these lariat RNAs is accompanied by the incidence of back-splicing of parent exons. Collectively, our results provide a comprehensive map of intron BPs and lariat RNAs in four plant species and uncover a link between lariat turnover and splicing.